Wage policy and endogenous wage rigidity: a representative view from the inside - Jonas Agell; Helge Bennmarker (Institute for Labour Market Policy Evaluation (IFAU), 2002)
We report the results from a representative survey of human resource managers in 885 Swedish firms. We estimate that during the severe recession of the 1990s, only 1.1 percent of workers took a cut in regular nominal pay. We trace the lack of wage moderation to a combination of exogenous (primarily labor law and collective bargaining contracts) and endogenous factors. Our analysis suggests that (i) endogenous wage rigidity plays an important role in most segments of the labor market, (ii) sources of endogenous wage rigidity differ significantly between the high- and low-end of the labor market, and between large and small firms, and (iii) mechanisms of wage rigidity tend to complement each other. Some of our questions deal with issues in the economics of personnel. We report evidence that job protection tends to reinforce the stigma from long-term unemployment, and that labor market training tends to reduce the same stigma. We show that managers in small organizations have a more negative attitude towards incentive schemes based on relative rewards, and we report evidence suggesting that gender have an impact on attitudes concerning effort and motivation.
Keywords: C81; E24; J30; J50; 330; Wage rigidity; survey evidence; effort models; motivation; labor law; long-term unemployment; gender and pay